PENGARUH SKEPTISISME PROFESIONAL AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris pada 3 KAP di Jakarta 2021) - Joy Putranami; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The purpose of this study is to determine the influence of the auditor's professional skepticism on the quality of the audit. This study collected quantitative data through the dissemination of questionnaires to external auditors as a sample of 30 respondents in KAP Karianton Tampubolon, KAP Warnoyo and Mennix, KAP Rama Wendra. Data analysis processing addresses descriptive anasythy, correlation coefficient, determination coefficient, t significance test and regression analysis. The results showed that the auditor's professional skepticism was good and conducted quality audit results. The significance test results showed a significant influence on the auditor's professional skepticism of audit quality at KAP Karianton Tampubolon, KAP Warnoyo and Mennix, KAP Rama Wendra.